Helmer Hanssens reiser i isbaksen. Med Roald Amundsen og polene som omdreiningspunkt - Aarekol, Lena (Nordlit, 2014)
Helmer Hanssen published his book Gjennem isbaksen. Atten år med Roald Amundsen in 1941. Five years earlier, in 1936, this book had been published in English with the title Voyages of a modern Viking. The Norwegian title of the book may be understood as a reflection of his polar life and almost lifelong relation to Amundsen; while the English title indicates more that Hanssen wanted to emphasis his own solid achievements in the Polar Regions. In earlier history studies Hanssen has been interpreted merely as the loyal assistant of Amundsen and as an eternal deuce. This article represents a new reading of Hanssen’s book up against previously known and unknown sources. This brings on new perspectives on the relation between Hanssen and Amundsen, but also on Hanssen himself, his relationship to his family, his perceptions of the Inuit people and his strong desire to go on a polar expedition. In this article, I argue that being the eternal deuce that is what, was Hanssen’s big chance. Amundsen gave him the possibility to experience pioneering expeditions and to see the world. My point is that Hanssen, even when living in the shadow of Amundsen, had his place in the outer circle of the spotlight.